2022
DOI: 10.3390/molecules27248948
|View full text |Cite
|
Sign up to set email alerts
|

Target Identification of 22-(4-Pyridinecarbonyl) Jorunnamycin A, a Tetrahydroisoquinoline Derivative from the Sponge Xestospongia sp., in Mediating Non-Small-Cell Lung Cancer Cell Apoptosis

Abstract: A dysregulation of the cell-death mechanism contributes to poor prognosis in lung cancer. New potent chemotherapeutic agents targeting apoptosis-deregulating molecules have been discovered. In this study, 22-(4-pyridinecarbonyl) jorunnamycin A (22-(4′py)-JA), a synthetic derivative of bistetrahydroisoquinolinequinone from the Thai blue sponge, was semisynthesized by the Steglich esterification method, and its pharmacological mechanism in non-small-cell lung cancer (NSCLC) was elucidated by a network pharmacolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 54 publications
0
13
2
Order By: Relevance
“…The upregulation of these proteins is associated with increased invasiveness and angiogenesis in cancers. , Inhibition of AKT activity has been shown to result in the downregulation of MMP-2 and MMP-9, consequently impeding cancer cell metastasis. , Additionally, AKT inhibition has been reported to attenuate the EGFR-mediated increase in VEGF and the endothelial tube-forming process. , In the context of this study, 22-(4′-py)-JA exhibits molecular signaling in lung cancer metastasis through the AKT/mTOR mechanism, effectively inhibiting EGF-mediating AKT/mTOR activation. It is worth noting that there is a crosstalk between AKT and ERK signaling, and a recent study demonstrated that 22-(4′-py)-JA suppressed ERK activity, contributing to apoptosis induction . However, in the present study, the phosphorylated ERK level was unaffected by a low dose of 22-(4′-py)-JA in suppressing cancer invasion and angiogenesis.…”
Section: Discussioncontrasting
confidence: 74%
See 4 more Smart Citations
“…The upregulation of these proteins is associated with increased invasiveness and angiogenesis in cancers. , Inhibition of AKT activity has been shown to result in the downregulation of MMP-2 and MMP-9, consequently impeding cancer cell metastasis. , Additionally, AKT inhibition has been reported to attenuate the EGFR-mediated increase in VEGF and the endothelial tube-forming process. , In the context of this study, 22-(4′-py)-JA exhibits molecular signaling in lung cancer metastasis through the AKT/mTOR mechanism, effectively inhibiting EGF-mediating AKT/mTOR activation. It is worth noting that there is a crosstalk between AKT and ERK signaling, and a recent study demonstrated that 22-(4′-py)-JA suppressed ERK activity, contributing to apoptosis induction . However, in the present study, the phosphorylated ERK level was unaffected by a low dose of 22-(4′-py)-JA in suppressing cancer invasion and angiogenesis.…”
Section: Discussioncontrasting
confidence: 74%
“…exhibits a promising anticancer activity . Evidence from in vitro studies shows that 22-(4′-py)-JA induces apoptosis in multiple NSCLC cell lines via an ERK/Bcl-2-dependent mechanism . The present study explores an antimetastasis activity and elucidates its underlying molecular mechanism.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations